Understanding level of CSR and Marketing in Albania in 2020 - Mateus Habili (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to understand the level of marketing and corporate social responsibility (CSR) based on the opinion of the citizens. Data were collected through surveys of 935 Albanians during the month of April in 2020. This is a description study based on primary and secondary source. The result shows that people think that the level of marketing is 1.0 and the level of CSR is the first level. The questions in the survey are easy to understand for all the people. The questions are camouflage from the real purpose and the people are answered how they think. In Albania there is a primitive form of marketing and CSR, because is a poor country and the people have essential problems and they think that they want the security and quality of product from a business.